Development of a design approach for two-degree of freedom gear train as power split device for series-parallel hybrid vehicle applications - Jose, Ralph San Gabriel (College of Engineering, University of the Philippines Diliman, 2014)
The power split device (PSD) is the heart of series-parallel hybrid vehicles. This powerbrain component uses two-degree of freedom gear train to transmit the combined power of the internal combustion engine and the motor-generators to the drive wheels. A new design approach is presented in this thesis with the aid of spreadsheet software, multi-variable solvers and self-developed search programs. Current hybrid vehicles commonly use sun-planet-ring configuration for their PSD. A new configuration using sun-planet-planet-sun arrangement for hybrid vehicle applications is presented in this study. The design approach is implemented to a case study to design the PSD of a specific series-parallel hybrid bus. The design procedure starts with the vehicle drive characterization followed by gear ratio refinement which is done to properly distribute the power requirements of the internal combustion engine and the motor-generators. There are many possible gear combinations that can satisfy the optimum gear ratio. The optimization stage of the design procedure gives the smallest and lightest possible gear trains that can handle the loads of the vehicle. Gears are selected from available standard gear sized and the most appropriate configuration is implemented. Using the developed design procedure, the sun-planet-planet-sun configuration with sun1, planet carrier, and sun2 connected to the engine and motor-generator1, the motor-generator2, and the output shaft respectively was selected for the specific bus application. The result of mass, size and kinematic analysis were verified using Creo Parametric 2.0.